The effect of ball possession on physical and technical performance in UEFA Champions League matches - Modric, T.; Versic, S.; Chmura, P.; Andrzejewski, M.; Konefal, M.; Raskovic, B.; Drid, P.; Sekulic, D. (Journal of Sports Sciences, 2022)
This study aimed to examine the effects of low-percentage ball possession teams (LPBPT) and high-percentage ball possession teams (HPBPT) on the physical and technical performance of UEFA Champions League (UCL) players. All data were obtained from group stage matches of UCL during the 2020/21 season using a semi-automatic optical tracking system. Linear mixed model was fitted with contextual variables as covariates. Wide midfielders and forwards in LPBPT covered more total distance, low-intensity running, and achieved greater average speed than in HPBPT (all large effect sizes [ES]). Central defenders and fullbacks covered more high-intensity running (small ES), while CMs covered more sprinting (medium ES) in HPBPT than in LPBPT. Players on all playing positions produced greater number of passes and successful passes in HPBPT than in LPBPT (large ES), except forwards who produced more passes in LPBPT than in HPBPT (small ES). Both physical and technical performance were highly dependent on ball possession percentages, with evident position-specific changes, indicating that the effect of ball possession is highly position-dependent. These findings provide information for soccer coaches on physical and technical demands across teams with varying percentage ball possession, which could be used to individualise training programs based on playing style and position.